STRUCTURE OF SPORT PERFORMANCE “STREET DANCE” (Fiep Bulletin - online, 2013)
The dance is one of the oldest expressive manifestations, and could represent the culture, religion and customs of a society. Besides allows physiological benefits and social interaction. The objective is to verify aspects of motivation and assess the levels of physical fitness of a group of children from public schools who practice the sport of Street Dance. The sample was composed of 58 people of both sexes (14±1.37 ) and the data was collected by means of closed questionnaire with questions on time and frequency of daily physical activity and their motivations and the data analysis was performed using the descriptive statistics. For the practice of the dance the result was that 64% of males and 48% of female train only once per day, and 41% male and 48% of female train two times per week. For physical fitness flexibility, we found 59% male and 37% female with qualified index above average in test abdominal strength 35% of men and only 10% of girls were above average in upper limb strength 30% males and 44% females were above average in agility test 47% male and 56% female was described as very poor in horizontal impulse, 18% males and 5% females were qualified with very good index. In the evaluation of body mass index (BMI), 70% male and 63% of females are found in the media and in the assessment of fat percentage, 59% male and 39% female was qualified as excellent. However more studies are needed on the physical contributions anthropometric and motor that this modality can provide the adepts.
Keywords: Street Dance; physical fitness; motivation.